18F‐FDG PET/MRI vs MRI in patients with recurrent adenoid cystic carcinoma. Issue 1 (13th December 2018) - Kirchner, Julian; Schaarschmidt, Benedikt M.; Sauerwein, Wolfgang; Deuschl, Cornelius; Arweiler‐Harbeck, Diana; Holtmann, Laura; Stebner, Vanessa; Umutlu, Lale; Antoch, Gerald; Ruhlmann, Verena
Abstract: Objectives: To evaluate and compare the diagnostic potential of 18 F‐fluorodeoxyglucose positron emission tomography/magnetic resonance imaging ( 18 FDG‐PET/MRI) and MRI for recurrence diagnostics after primary therapy in patients with adenoid cystic carcinoma (ACC). Methods: A total of 32 dedicated head and neck 18 F‐FDG PET/MRI datasets were included in this analysis. MRI and 18 F‐FDG PET/MRI datasets were analyzed in separate sessions by two readers for tumor recurrence or metastases. Results: Lesion‐based sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were 96%, 84%, 90%, 93%, and 91% for 18 F‐FDG PET/MRI and 77%, 94%, 95%, 73%, and 84% for MRI, resulting in a significantly higher diagnostic accuracy of 18 F‐FDG PET/MRI compared to MRI ( P < .005). Conclusion: 18 F‐FDG PET/MRI is superior to MRI in detecting local recurrence and metastases in patients with ACC of the head and neck. Especially concerning its negative predictive value, 18 F‐FDG PET/MRI outperforms MRI.